Areca nut (Areca catechu) husks and Luffa (Luffa cylindrica) sponge as microbial immobilization matrices for efficient phenol degradation. (February 2020) - Bera, Sounak; Mohanty, Kaustubha
Graphical abstract: Highlights: A mixed bacterial culture was immobilized on areca nut husks and luffa sponge fibers. Effect of physical parameters on degradation rate of phenol was studied. Modeling and kinetics of phenol degradation was carried out. Bio-kinetic parameters were calculated via nonlinear regression analysis in MATLAB. Immobilized cells could be stored without any special treatment. Abstract: Immobilization of microorganisms is a widely adopted strategy for the efficient degradation of hazardous organic compounds like phenol. Microorganisms can be immobilized in synthetic or natural matrices. In this work dried areca nut ( Areca catechu ) husks and luffa ( Luffa cylindrica ) sponge fibers were used as alternative and inexpensive natural matrices for microbial cell immobilization. The potential of these immobilization systems for the effective bioremediation of phenolic wastewater was explored. A bacterial consortium was isolated by enriching a sludge sample from a petroleum refinery in high phenol concentrations. The mixed bacterial culture was capable of degrading 1000 mg L −1 of phenol in suspension cultures. The bacterial consortium was immobilized on the lignocellulosic matrices. Phenol degradation studies were performed in batches to optimize the physicochemical parameters. Optimum pH and temperature for phenol degradation was found to be 8.0 and 37 °C. At an optimum pH and temperature, the areca nut husk and luffa sponge systems immobilized with the mixed culture could degrade 1000 mg L −1 phenol in 28 h and 30 h respectively. The highest experimental degradation rates in areca nut husk and luffa sponge systems were 0.37 h −1 and 0.21 h −1 respectively at 200 mg L −1 phenol. Degradation kinetic studies were carried out using several inhibition models. Further studies revealed that both matrices with immobilized microbes could be reused for several successive batch degradation experiments and stored at 4 °C for several weeks without any noticeable loss in degradation efficiency.